2021
DOI: 10.3390/ph14070650
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Activity of Isoquinolone Derivatives against Influenza Viruses and Their Cytotoxicity

Abstract: Influenza viruses are one of the major causative agents for human respiratory infections. Currently, vaccines and antivirals approved for preventing and treating viral infections are available. However, limited protection efficacy and frequent emergence of drug-resistant viruses stand for a need for the development of antivirals with different chemical skeletons from existing drugs. Screening of a chemical library identified an isoquinolone compound (1) as a hit with 50% effective concentrations (EC50s) betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…As a member of the isoquinoline alkaloid family, isoquinolinones have exhibited a wide range of structural diversity and biological activity [ 6 , 7 ], and gliquidone is used as a commercial drug to treat diabetes ( Figure 1 , I ) [ 8 ]. It was also found that isoquinolinones exhibit antiviral ( Figure 1 , II ) [ 9 ], anticancer ( Figure 1 , III ) [ 10 ], and anti-metastatic biological activities ( Figure 1 , IV ) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a member of the isoquinoline alkaloid family, isoquinolinones have exhibited a wide range of structural diversity and biological activity [ 6 , 7 ], and gliquidone is used as a commercial drug to treat diabetes ( Figure 1 , I ) [ 8 ]. It was also found that isoquinolinones exhibit antiviral ( Figure 1 , II ) [ 9 ], anticancer ( Figure 1 , III ) [ 10 ], and anti-metastatic biological activities ( Figure 1 , IV ) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the new synthesized NHC analogs in hands, we investigated antiviral activity against SARS-CoV-2 (BetaCoV/Korea/KCDC-03/2020) in Vero cells (Vero CCL-81 cells), DENV-2 replicon BHK-21 (DENV2-BHK) cells, and Flu A/Puerto Rico/8/34 (PR8; H1N1), Flu A/Hong Kong/8/68 (HK; H3N2), and Flu B/Lee/40 (Lee) in MDCK cells (CCL-34) according to the previously reported methods. 33 , 34 , 35 Cell viability of non-infected or infected cells was measured using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazoliumbromide (MTT) to determine the half-maximal cytotoxic concentration (CC 50 ). For dengue virus, the half-maximal effective concentration (EC 50 ) was determined by using Renilla Luciferase assay system.…”
mentioning
confidence: 99%